Changing trends of antibiotic resistance in neonatal sepsis in a tertiary care hospital - S., Pauline Packiaseeli; T., Ashok Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Sepsis and other infections cause 15% neonatal deaths in India. The present study is to determine the resistance pattern of pathogens causing neonatal sepsis and to provide antibiogram to pediatricians for better patient management. Methods: Positive Blood culture reports of neonatal sepsis cases detected during the years 2014 and 2015 were studied. The antibiotic resistance of the organisms found during the years 2014 and 2015 were compared by calculating the probability (p value) using the standard formula. Results: Coagulase negative staphylococci (CONS) was the most common organism in 2014 whereas pseudomonas was predominant in 2015.Resistance of CONS to amoxycillin and ceftrioxone has significantly increased in 2015.Also resistance of CONS to vancomycin was noted. Resistance of Pseudomonas to cefuroxime, ceftazidime and amoxicillin/clavulanuic acid combination were increased but not significantly. There was also emerging resistance of pseudomonas to gentamicin and amikacin. Resistance of acinetobacter to cefuroxime, ceftrioxone and gentamicin has increased in 2015 but not significantly. Citrobacter showed a significant increase in resistance to amoxicillin/clavulanic acid combination (p=0.006). Conclusions: Bacterial spectrum causing neonatal sepsis varies in different regions, varies in the same site during different time periods, also their antibiotic resistance pattern varies in different regions and changes constantly. Increase in resistance to commonly used antibiotics stress the need of rational use of antibiotics.